Integrasi teknologi dalam pendidikan anak usia dini: menilai dampaknya pada perkembangan kognitif - Salim, Nur Agus (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2022)
This research aims to evaluate the impact of technology integration in early childhood education on their cognitive development. Using a literature review, this research observes the use of technology in the classroom and analyzes data from research results and literature. The results show that technology, when used in a balanced and age-appropriate manner, supports improved cognitive skills such as language and problem solving. However, misuse or overuse can negatively impact a child's social and emotional skills. The study's conclusions emphasize the importance of structured and supervised use of technology in early childhood education, suggesting a balance between technology use and traditional learning activities to support holistic and healthy cognitive development.